Mapping CH4 : CO2 ratios in Los Angeles with CLARS-FTS from Mount Wilson, California - K. W. Wong; D. Fu; T. J. Pongetti; S. Newman; E. A. Kort; R. Duren; Y.-K. Hsu; C. E. Miller; Y. L. Yung; S. P. Sander (Atmospheric Chemistry and Physics, 2015)
The Los Angeles megacity, which is home to more than 40% of the population in California, is the second largest megacity in the United States and an intense source of anthropogenic greenhouse gases (GHGs). Quantifying GHG emissions from the megacity and monitoring their spatiotemporal trends are essential to be able to understand the effectiveness of emission control policies. Here we measure carbon dioxide (CO2) and methane (CH4) across the Los Angeles megacity using a novel approach – ground-based remote sensing from a mountaintop site. A Fourier transform spectrometer (FTS) with agile pointing optics, located on Mount Wilson at 1.67 km above sea level, measures reflected near-infrared sunlight from 29 different surface targets on Mount Wilson and in the Los Angeles megacity to retrieve the slant column abundances of CO2, CH4 and other trace gases above and below Mount Wilson. This technique provides persistent space- and time-resolved observations of path-averaged dry-air GHG concentrations, XGHG, in the Los Angeles megacity and simulates observations from a geostationary satellite. In this study, we combined high-sensitivity measurements from the FTS and the panorama from Mount Wilson to characterize anthropogenic CH4 emissions in the megacity using tracer–tracer correlations. During the period between September 2011 and October 2013, the observed XCH4 : XCO2 excess ratio, assigned to anthropogenic activities, varied from 5.4 to 7.3 ppb CH4 (ppm CO2)−1, with an average of 6.4 ± 0.5 ppb CH4 (ppm CO2)−1 compared to the value of 4.6 ± 0.9 ppb CH4 (ppm CO2)−1 expected from the California Air Resources Board (CARB) bottom-up emission inventory. Persistent elevated XCH4 : XCO2 excess ratios were observed in Pasadena and in the eastern Los Angeles megacity. Using the FTS observations on Mount Wilson and the bottom-up CO2 emission inventory, we derived a top-down CH4 emission of 0.39 ± 0.06 Tg CH4 year−1 in the Los Angeles megacity. This is 18–61% larger than the state government's bottom-up CH4 emission inventory and consistent with previous studies.